THERMAL HYDRAULIC SYSTEM AND NUMERICAL MODELLING OF VVER-1000 NUCLEAR REACTOR IN VIEW OF THE 1ST NINH THUAN NUCLEAR POWER PLANT - DUONG , NGOC HAI; NGUYEN , TAT THANG (Nuclear Science and Technology, 2011)
This paper presents an overview of the thermal-hydraulic system of Russian VVER-1000 pressurized water reactors (PWRs) and some results of our study on the numerical simulation using VISA_RELAP5 integrated code. This research has been carried out in view of the 1st nuclear power plant of Vietnam that will use VVER type reactors. It should be noted that knowledge of the VVER reactor system is still lacking in Vietnam now. The data that we used in our research is real data of the Kalinin nuclear power plant (NPP) in Russia. Therefore this research has important practical implications especially for the preparation for the safe operation and proper management of incidents (accidents) for the 1st NPP of Vietnam.